Diagnosing a hematopoietic malignancy during shoulder arthroplasty - Orhan, Özlem; Sezgin, Erdem Aras; Tokgöz, Mehmet Ali; Çakmak, Pınar; Kanatlı, Ulunay (Vojnosanitetski pregled, 2022)
Introduction. Determining the cause of shoulder pain is usually a challenge as many problems, such as rheumatoid arthritis, osteoarthritis, osteonecrosis, rotator cuff arthropathy, traumatic arthritis, fractures, conditions of cervical vertebra, and neoplasms, can produce similar symptoms. The diagnosis is usually regarded as incidental, however, chronic lymphocytic leukemia (CLL) diagnosis by the histopathological evaluation performed on lymph nodes excised during a shoulder procedure has not been reported in the literature, to the best of our knowledge. We present a CLL-small lymphocytic lymphoma (SLL) case diagnosed incidentally during reverse shoulder arthroplasty. Case report. A 69-year-old female with a history of left proximal humerus fracture a year prior was presented to our outpatient clinic with left shoulder pain. A proximal humerus non-union was revealed radiographically. The patient underwent reverse shoulder arthroplasty. During surgery, a 2.5 × 1.5 × 1 cm sized lymph node was observed near the left cephalic vein. The lymph node biopsy result was reported to be CLL-SLL. The patient had no early postoperative complications and was discharged two days after. At her final evaluation, she was free of orthopedic complaints and was consulted with the hematology department to receive CLL-SLL treatment. Conclusion. Elderly patients presenting with non-union should be questioned for vague symptoms; lymph nodes surrounding the non-union site should be examined thoroughly. Any suspicious lymphadenopathy encountered during orthopedic surgery should be excised and sent for pathological evaluation.